Raku firing advanced techniques - Jones, Bill. (Westerville, Ohio American Ceramic Society, 2009)
Advanced techniques in raku firing; covers production, kiln construction, glaze formulation, tools and more.
Raku then and now / Hal Riegger -- Discovering naked raku / Kate and Will Jacobson -- Marcia Selsor: raku-fired slabs / Louana Lackey -- Raku at Amatlan / Hilda San Vicente Tello -- Inlaid glass technique / Steven Branfman -- Successful raku / John Ramer Sherrill -- Billy Ray Mangham: reconnecting with the species / Gary C. Hatcher -- CJ Buckner: raku menagerie / Henry Atwater -- Floral imagery on raku fans / Marcia Jestaedt -- New beginnings / Beth Cavener Stichter -- Production raku kiln / Ronda M. Liskey -- Alternative raku kilns / Andreas Salzman with Jennifer Salzman -- Wood-fired raku kiln / Nesrin During -- Wood firing basics / W. Lowell Baker -- Portable fiber raku kiln / Daryl Baird -- Portable gas raku kiln / George Juliano with Elizabeth Hudgins -- Raku glazes / Harold J. McWhinnie -- Designing a matt red raku glaze / Tom Buck -- Valdez flashfiring / John Ramer Sherrill -- Interference colors with copper raku / R.W. Burrows -- Raku color and opacity / Jeff Zamek -- Raku glaze trials / Lila Bakke -- Raku clays / Bill Jones -- Large-scale raku / Carl Gillberg -- In pursuit of form / Kristin Doner -- Raku reduction stenciling / Jerry L. Caplan -- Ramon Camarillo: a marraige [sic] of three cultures / Cathy Grubman -- Michael Lancaster: reinventing oneself / Hollis Walker -- The nichrome wire solution / Cory Pinassi -- Neoclassical raku / Robert Hasselle -- Large raku platters / Tom Radca.
Keywords: Raku pottery -- Technique; Firing (Ceramics).; Glazes -- Formulae; Kilns